The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1097/qai.0000000000001176
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Adolescent Engagement in Antenatal Care and Prevention of Mother-to-Child HIV Transmission Services in Kenya

Abstract: Background Rates of pregnancy and HIV infection are high among adolescents. However, their engagement in prevention of mother-to-child HIV transmission (PMTCT) services is poorly characterized. We compared engagement in the PMTCT cascade between adult and adolescent mothers in Kenya. Methods We conducted a nationally representative cross-sectional survey of mother–infant pairs attending 120 maternal child health clinics selected by probability proportionate to size sampling, with a secondary survey oversampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 25 publications
1
73
0
Order By: Relevance
“…Younger mothers were significantly more likely to have children <12 months of age who were, in turn, more likely to have high VL; however, even in multivariable models adjusted for child's age and VL, maternal age was still a significant predictor of VS. While lower VS for children with younger mothers has not been previously reported, existing data show that younger women are less likely to complete PMTCT and to be retained in care . It is possible that the poor treatment outcomes among young mothers has an impact on their children's health; however, this question warrants further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…Younger mothers were significantly more likely to have children <12 months of age who were, in turn, more likely to have high VL; however, even in multivariable models adjusted for child's age and VL, maternal age was still a significant predictor of VS. While lower VS for children with younger mothers has not been previously reported, existing data show that younger women are less likely to complete PMTCT and to be retained in care . It is possible that the poor treatment outcomes among young mothers has an impact on their children's health; however, this question warrants further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…[13] Briefly, we used probability proportionate to size sampling to select 121 MCH clinics in seven of the eight geographical regions in Kenya from which all mother-infant pairs were sampled to participate during a 5-day period per clinic. We classified facility size based on annual number of ANC clinic visits in 2011 and excluded “small” (<500 visits) and/or North Eastern Province facilities due to logistical constraints.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…Adolescents and young adults had specific expectations of transition services; as reported in Burkina Faso, reaching adulthood raises particular problems for HIV-infected adolescent females with the issues of relationship to self (biographical disruption and jeopardized female identity) and to others (weakening of social ties in situations of dependency and of pursuit of social advancement, marriage and procreation) [32]. In one study, female adolescents and youth engagement in the prevention of mother-to-child HIV transmission (PMTCT) services showed that they had poorer antenatal care attendance and uptake of ART compared to adult pregnant women [36]. This vulnerability needs to be taken into account when managing the transition process [32].…”
Section: Barriers Facilitators Expectations and Needs Associated Wimentioning
confidence: 99%